Circular RNAs associated with a mouse model of concanavalin A‐induced autoimmune hepatitis: preliminary screening and comprehensive functional analysis. Issue 11 (14th October 2020) - Liu, Yang; Li, Zhencheng; Hao, Jianheng; Chen, Hao; Hou, Tiezheng; Hao, Huiqin
Abstract : Without treatment, autoimmune hepatitis (AIH) often leads to cirrhosis, liver failure and, in some cases, death. However, the pathogenesis of AIH remains incompletely understood. Here, we explored the relationship between differentially expressed circular RNAs (DECs) and development of AIH by obtaining an expression profile of DECs in a concanavalin A‐induced AIH mouse model by microarray. In total, we identified 27 DECs; the host genes of these DECs were annotated with 140 Gene Ontology terms and 19 pathways, revealing potential roles in the metabolism of cellular ions and regulation of protein expression, as well as possible involvement in endocytosis and apoptosis. We constructed a circular RNA–microRNA network that was used to infer that a mmu_circ_0001520/mmu‐miR‐193b‐3p/MAPK10 network may be associated with the occurrence of AIH. These findings may help lay the foundation for validation of the potential roles of circular RNAs in AIH. Abstract : Here, we investigated differentially expressed circular RNAs in a concanavalin A ‐induced AIH mouse model with microarray, identifying differentially expressed circular RNAs that may play crucial roles in the pathogenesis of AIH. These candidates may have potential for development into novel therapeutic biomarkers for this disorder.